Numerical Simulation of Defect Inspection Using Electromagnetically Stimulated Thermography - 刘国飞 李国华 (Shanghai jiao tong da xue xue bao, 2011)
The feasibility of electromagnetically stimulated thermography non-destructive testing （NDT） for the detection of defects in metallic conductive materials has been carried out by finite element analysis. Aluminum plates with defects of different diameters, depths, locations, shapes and orientation with respect to eddy current are numerically investigated. ANSYS software is used to solve the coupled electromagnetic and temperature field equations. The peak temperatures on the top surface of circular defects with different diameters and depths are calculated at varying excitation frequencies. It is demonstrated that the obtained temperature inreases with increase of the defect diameter and decrease of its depth. The dependence of the temperature over the top surface of the defect on its location and orientation is also presented. The results indicate that we can detect the subsurface defect and estimate its depth and location by choosing a suitable coil-specimen configuration.